Composition, Chemical Fingerprinting and Antimicrobial Assessment of Costa Rican Cultivated Guavas (Psidium friedrichsthalianum (O. Berg) Nied. and Psidium guajava L.) Essential Oils from Leaves and Fruits - Granados Chinchilla, Fabio (2016)
The essential oil of two related tree species, P. friedrichsthalianum and P. guajava, where obtained. A total of six different oil samples were recovered including leaves in dry/rainy season and fruits of both plant species. Oil yields ranged between 0.128% (P. friedrichsthalianum leaves during dry season)-0.743% (P.guajava leaves during rainy season). All extracts were subjected to a GC/MS analysis using, during the chromatographic separation, a polyethylene glycol column. In general terms, we recognized three independent biosynthetic routes i. aromatic compounds ii. Terpenes and iii.Fatty acids derivatives. Several compound were found to be preserved in several of the oils such as 2,4-di-tert-butylphenol, α-terpineol and neointermedeol whereas Costa Rican guava fruit exhibit unique compounds such as 2H-pyran-2,6-(3H)-dione. Terpenes and fatty acids are among the most variable (p<0.005) in content when comparing dry season with rainy season leaves. Finally, based on profiling, a descriptive PCA analysis showed three related groups and that Costa Rican guava fruit oil as the most different in terms of composition. Herein we report more than 50 compounds for each species and relative percentages of major components (>0.1%) and trace compounds. In addition, we evaluated the antimicrobial activity of these essential oils against common foodborne and food-spoilage related bacteria. The rainy season P. guajava leafs’ presented the highest antimicrobial activity against all the bacteria strains tested, with inhibition zones ranging from 31 to 52 mm. This study will help understand volatile composition of a fruit producing plant native from this geographic area and hints toward possible applications.